2019
DOI: 10.30773/pi.2019.01.10.1
|View full text |Cite
|
Sign up to set email alerts
|

Temperament and Character Profiles Associated with Internalizing and Externalizing Problems in Children with Attention Deficit Hyperactivity Disorder

Abstract: Objective This study aimed to identify temperament and character profiles associated with internalizing and externalizing problems in children with attention deficit hyperactivity disorder (ADHD). Methods Children with ADHD (n=114, 8.51±1.87 years) were selected from the Department of Child and Adolescent Psychiatry at Jeju National University Hospital. They were diagnosed by Kiddie-Schedule for Affective Disorders and Schizophrenia-Present and Lifetime Version and eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 33 publications
0
6
0
1
Order By: Relevance
“…Hence, the characteristics of ADHD may increase both the risk for and the vulnerability to insufficient sleep. There are documented associations between various domains of sleep and both internalizing/externalizing symptoms and the negative impacts of these symptoms on youth with ADHD [45][46][47][48] . However, we know little about the nature of the associations between sleep and these symptoms in youth with ADHD.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the characteristics of ADHD may increase both the risk for and the vulnerability to insufficient sleep. There are documented associations between various domains of sleep and both internalizing/externalizing symptoms and the negative impacts of these symptoms on youth with ADHD [45][46][47][48] . However, we know little about the nature of the associations between sleep and these symptoms in youth with ADHD.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the family environment may be relevant for the course of various mental and psychological diseases and ultimately clinical outcomes, including major depressive disorder ( 32 ), trichotillomania, obsessive–compulsive disorder ( 33 ), and ADHD ( 23 ). Character profiles are correlated with individual differences in goals and values, which are based on learning and the perceptions of self and others ( 34 ). The character traits of parents, as an important family environment factor, exhibit a remarkable influence on children's emotional and behavioral development ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…The character traits of parents, as an important family environment factor, exhibit a remarkable influence on children's emotional and behavioral development ( 35 ). Most previous studies have demonstrated the temperament and character profiles associated with ADHD and could be used to distinguish ADHD from comorbid disease ( 34 , 36 , 37 ). However, the relationship between the character traits of parents in children with ADHD and clinical or academic outcomes into adulthood remains relatively understudied.…”
Section: Discussionmentioning
confidence: 99%
“…In questi casi il paziente è spesso a conoscenza delle regole di comportamento adeguate pur non riuscendo a metterle in pratica. Frequente è la manifestazione di ulteriori deficit di esternalizzazione che rende ancora più difficile l'approccio terapeutico (38).…”
Section: Procedures Diagnostiche In Caso DI Comorbiditàunclassified